Преимагинальные фазы развития и систематическое положение комара-долгоножки Tipula (? subgen.) decipiens Cz. (Diptera, Tipulidae) - Савченко, Е.Н. (Вестник зоологии, 1967)
The larvae of Tipula decipiens C z. live in a wet broken stone at the bottom of small mountain brooks in the beech forests, come of IV instar in autumn and stay to winter here. Their body organization is very alike to that of the larvae Tipula fulvipennis Deg. and T. maxima Poda, from which they differ, mainly, in strongly reduced lower fore pair of anal gills, having an appearance of small epidermic protrusions.
The larvae of T. decipiens pupate after wintering, next spring.
These pupae differ from T. fulvipennis and T. maxima in having at the base of dorso-caudal spines of the anal segment the small additional spinae.
On the basis of immature stages structure T. decipiens has to be included into the subgenus Acutipula A 1., as beittg its aberrant species.